Pentingnya Perencanaan Keuangan Yang Cerdas dan Efektif Di Era Pandemi Covid 19 - Mappadang, Agoestina; Sinaga, Melan (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Income received on a fixed or variable basis and expenses incurred must be managed properly and effectively. The principle of good financial management is if the expenditure of funds does not exceed the receipt of funds. Sources of funding received can come from debt or from income or business or investment. How plan finances in the current Covid-19 pandemic era are important, this is because the current pandemic period makes many people experience financial difficulties due to declining sources of income. Recording receipts and expenses or making a budget is a wise action in the midst of this difficult covid pandemic situation. Making a budget will be able to control which items must be prioritized and which must be considered. This problem should be felt by the customers of Auto 2000 BSD City, PT. Astra International, Tbk is the place where community service activities are carried out. Customers or customers do not understand how and how to manage finances well and do not understand the importance of making good financial planning. As a result of this ignorance, it results in ineffective finances and a deficit so that there are needs that cannot be met. The method used in the implementation of this service is to provide counseling in the form of presentations and assistance with budgeting. The results of this socialization activity are the customers of PT. Astra International Tbk is able to understand good financial management and is able to make personal financial planning.